2008
DOI: 10.1002/adma.200702586
|View full text |Cite
|
Sign up to set email alerts
|

Surface Gradient of Functional Heparin

Abstract: A gradient of functional heparin is fabricated onto a surface chemical gradient of plasma‐polymerized allyl amine (see figure). While heparin functionality changes across the gradient, increased adsorption of heparin onto the surface is not accompanied with a continued, corresponding rise in heparin function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 29 publications
3
73
0
Order By: Relevance
“…This ability to plasma-treat surfaces with two monomers concurrently to facilitate conjugation to aldehyde groups while preventing physisorptive attachment elsewhere, in one step and without blocking, is a very important consideration for the fabrication of bioconjugation platforms. Since others have shown that protein adsorption to plasma polymer surfaces may result in protein denaturation, 18,29 in the final section we demonstrate that our prepared gradient surfaces exhibit retention of SAV binding capability.…”
Section: ■ Discussionmentioning
confidence: 87%
“…This ability to plasma-treat surfaces with two monomers concurrently to facilitate conjugation to aldehyde groups while preventing physisorptive attachment elsewhere, in one step and without blocking, is a very important consideration for the fabrication of bioconjugation platforms. Since others have shown that protein adsorption to plasma polymer surfaces may result in protein denaturation, 18,29 in the final section we demonstrate that our prepared gradient surfaces exhibit retention of SAV binding capability.…”
Section: ■ Discussionmentioning
confidence: 87%
“…[19] Significantly, Robinson et al report that heparin can be adsorbed to the positively charged surface of plasma polymerized allylamine films based on their electrostatic interaction. [21] Such non-covalently immobilized heparin retains excellent activity and its protein-binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…The biotinylated Link module from human TSG-6 (bA-Link_TSG6 (26) denoted here as GAG-BP), a well characterized GAG-binding domain (27), was used in a colorimetric assay to determine the amount of functional heparin/HS adsorbed onto 0.6-cm 2 uncoated and ppAm scaffolds as described previously for two-dimensional surfaces (2022, 28). For details, see supplemental “Experimental Procedures.”…”
Section: Methodsmentioning
confidence: 99%